Forecasting Cyber Threat Landscapes in Indonesia (2025-2026): A Predictive Analysis Using the MITRE ATT&CK Framework - Adji Kusuma; Suhirwan; Agus H Sulistyono Reksoprodjo (Cita konsultindo, 2026)
As Indonesia accelerates its digital transformation under the